Restoration and Possible Upgrade of a Historical Motorcycle Part Using Powder Bed Fusion - Kudrna, Lukas; Ma, Quoc-Phu; Hajnys, Jiri; Mesicek, Jakub; Halama, Radim; Fojtik, Frantisek; Hornacek, Lukas (Materials (Basel, Switzerland), 2022)
Reverse engineering is the process of creating a digital version of an existing part without any knowledge in advance about the design intent. Due to 3D printing, the reconstructed part can be rapidly fabricated for prototyping or even for practical usage. To showcase this combination, this study presents a workflow on how to restore a motorcycle braking pedal from material SS316L with the Powder Bed Fusion (PBF) technology. Firstly, the CAD model of the original braking pedal was created. Before the actual PBF printing, the braking pedal printing process was simulated to identify the possible imperfections. The printed braking pedal was then subjected to quality control in terms of the shape distortion from its CAD counterpart and strength assessments, conducted both numerically and physically. As a result, the exterior shape of the braking pedal was restored. Additionally, by means of material assessments and physical tests, it was able to prove that the restored pedal was fully functional. Finally, an approach was proposed to optimize the braking pedal with a lattice structure to utilize the advantages the PBF technology offers.
Keywords: SS316L; 3D scanning; lattice structure; electronic speckle pattern interferometry; printing simulation; reverse engineer; powder bed fusion